(untitled) (Al Dzahab, 2022)
Purpose: To determine the effect of discounts, promotions and shopping lifestyle partially or simultaneously on impulse buying at online shops at STIE Sakti Alam Kerinci students. Design/methodology/approach: The population in this study were students at STIE Sakti Alam Kerinci. The sample for this study amounted to 90 respondents with the Convinience Sampling sampling technique. The data analysis tools used are Likert Scale, Multiple Linear Regression Analysis, Partial and Simultaneous Coefficient of Determination, t-test and F-test. Findings: The results showed that both partially and simultaneously Discount, Promotion, and Shopping lifestyle had a significant and positive effect on impulse buying. Research implications: The results of this study provide an overview for online business actors so that they can pay attention to the shopping style of consumers, namely by providing the best discounts and promotions to attract the interest of these consumers.